Effect Of Human Resource Capacity On Village Fund Management Via Anti-Corruption Numeracy Mediation Variable - Ilham; Aqfir; Messa, Samsuddin Beddu Messa (Jurnal Manajemen Dayasaing, 2025)
This study examines how improvements in human resource capacity affect the performance of village fund management, with anti-corruption numeracy as a mediating variable. Three hypotheses are tested: the direct effect of human resource capacity on village fund management, the indirect effect through anti-corruption numeracy, and the direct effect of anti-corruption numeracy on fund management performance. The research uses a quantitative approach with a survey method. The study was conducted in North Tolitoli District, Central Sulawesi, involving 121 village officials from six randomly selected villages. Data were analyzed using path analysis and the Sobel test. The results confirm that all hypotheses are statistically supported. Human resource capacity has a significant direct effect (β = 0.677; p < 0.001) and an indirect effect through anti-corruption numeracy (Sobel = 3.109; p = 0.001). Anti-corruption numeracy also shows a direct influence on village fund management (β = 0.303; p < 0.001). These findings suggest that enhancing capacity and anti-corruption awareness are key to improving transparent and accountable village fund governance.